Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's solve the recurrence relation \( A(n+1) = A(n) - 19 \) for \( n \geq 1 \) with the initial condition \( A(1) = -6 \).
1. Initial Condition:
Start with the initial condition \( A(1) = -6 \). This gives us the first term:
[tex]\[ A(1) = -6 \][/tex]
2. Applying the Recurrence Relation:
To find \( A(2) \), use the recurrence relation \( A(n+1) = A(n) - 19 \) with \( n = 1 \):
[tex]\[ A(2) = A(1) - 19 = -6 - 19 = -25 \][/tex]
Next, to find \( A(3) \), use the recurrence relation with \( n = 2 \):
[tex]\[ A(3) = A(2) - 19 = -25 - 19 = -44 \][/tex]
Then, to find \( A(4) \), use the recurrence relation with \( n = 3 \):
[tex]\[ A(4) = A(3) - 19 = -44 - 19 = -63 \][/tex]
Finally, to find \( A(5) \), use the recurrence relation with \( n = 4 \):
[tex]\[ A(5) = A(4) - 19 = -63 - 19 = -82 \][/tex]
3. Summary of Results:
We have calculated the following terms:
[tex]\[ A(1) = -6, \quad A(2) = -25, \quad A(3) = -44, \quad A(4) = -63, \quad A(5) = -82 \][/tex]
Therefore, the sequence \( \{A(n)\} \) for \( n = 1, 2, 3, 4, 5 \) is:
[tex]\[ [-6, -25, -44, -63, -82] \][/tex]
This sequence was generated by repeatedly applying the recurrence relation starting from the initial condition.
1. Initial Condition:
Start with the initial condition \( A(1) = -6 \). This gives us the first term:
[tex]\[ A(1) = -6 \][/tex]
2. Applying the Recurrence Relation:
To find \( A(2) \), use the recurrence relation \( A(n+1) = A(n) - 19 \) with \( n = 1 \):
[tex]\[ A(2) = A(1) - 19 = -6 - 19 = -25 \][/tex]
Next, to find \( A(3) \), use the recurrence relation with \( n = 2 \):
[tex]\[ A(3) = A(2) - 19 = -25 - 19 = -44 \][/tex]
Then, to find \( A(4) \), use the recurrence relation with \( n = 3 \):
[tex]\[ A(4) = A(3) - 19 = -44 - 19 = -63 \][/tex]
Finally, to find \( A(5) \), use the recurrence relation with \( n = 4 \):
[tex]\[ A(5) = A(4) - 19 = -63 - 19 = -82 \][/tex]
3. Summary of Results:
We have calculated the following terms:
[tex]\[ A(1) = -6, \quad A(2) = -25, \quad A(3) = -44, \quad A(4) = -63, \quad A(5) = -82 \][/tex]
Therefore, the sequence \( \{A(n)\} \) for \( n = 1, 2, 3, 4, 5 \) is:
[tex]\[ [-6, -25, -44, -63, -82] \][/tex]
This sequence was generated by repeatedly applying the recurrence relation starting from the initial condition.
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.